2022
DOI: 10.1101/2022.04.26.489580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diet induced obesity and type 2 diabetes drives exacerbated sex-associated disease profiles in K18-hACE2-mice challenged with SARS-CoV-2

Abstract: SARS-CoV-2 infection results in wide-ranging disease manifestation from asymptomatic to potentially lethal. Infection poses an increased threat of severity to at-risk populations including those with hypertension, diabetes, and obesity. Type 2 Diabetes (T2DM), is characterized, in part, by insulin insensitivity and impaired glucose regulation. T2DM patients have increased disease severity and poorer outcomes with COVID-19. We utilized the diet-induced obesity (DIO) model of Type 2 Diabetes in SARS-CoV-2-suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…4B). Lastly, to define immune correlates of protection, we assessed humans, establishing this model as a viable option for studying the relationship between metabolic disease and SARS-CoV-2 vaccine response [19][20][21] . Here, we developed a mouse model of metabolic disease by feeding mice a HFD, which led to obesity, hyperinsulinemia, and glucose intolerance.…”
Section: Sars-cov-2 Mrna Vaccine Protects Nd Mice But Not Hfd Mice Fr...mentioning
confidence: 99%
See 1 more Smart Citation
“…4B). Lastly, to define immune correlates of protection, we assessed humans, establishing this model as a viable option for studying the relationship between metabolic disease and SARS-CoV-2 vaccine response [19][20][21] . Here, we developed a mouse model of metabolic disease by feeding mice a HFD, which led to obesity, hyperinsulinemia, and glucose intolerance.…”
Section: Sars-cov-2 Mrna Vaccine Protects Nd Mice But Not Hfd Mice Fr...mentioning
confidence: 99%
“…Further, DIO mice mounted impaired immune responses following immunization with subunit or inactivated-virus influenza vaccines, including decreased antibody (Ab) titers relative to controls, lower CD8 + T cell levels, impaired protection from live viral challenge, and greater waning in humoral immunity [15][16][17][18] . Additionally, studies of MERS-CoV and SARS-CoV-2 infection have found that DIO mice exhibit increased lung titers and/or greater morbidity and mortality following live-virus challenge relative to controls [19][20][21] . However, little is known regarding the effects of obesity and hyperglycemia on SARS-CoV-2 vaccine responses.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has been identified as an independent risk factor for severe COVID‐19 14–18 and has been associated with chronic systemic inflammation 19,20 . However, most of these inferences are correlative and are based either on data from epidemiological studies 7,8,11,15,17 or from studies performed in nonnatural hosts of SARS‐CoV‐2 21,22 . Therefore, a relevant model of coronavirus infection, which mimics SARS‐CoV‐2 infection in humans, is needed to study the impact of obesity on coronavirus disease outcome.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 However, most of these inferences are correlative and are based either on data from epidemiological studies 7,8,11,15,17 or from studies performed in nonnatural hosts of SARS-CoV-2. 21,22 Therefore, a relevant model of coronavirus infection, which mimics SARS-CoV-2 infection in humans, is needed to study the impact of obesity on coronavirus disease outcome. We hypothesized that this model would be useful for identifying biomarkers associated with disease severity in COVID-19 patients, which could have prognostic value for risk stratification of patients with COVID-19.…”
mentioning
confidence: 99%
“…Obesity has been identified as an independent risk factor for severe COVID-19 [14][15][16][17][18] and has been associated with chronic systemic inflammation 19,20 . However, most of these inferences are correlative and are based either on data from epidemiological studies 7,8,11,15,17 or from studies performed in non-natural hosts of SARS-CoV-2 21,22 . Therefore, a relevant model of coronavirus infection, which mimics SARS-CoV-2 infection in humans, is needed to study the impact of obesity on coronavirus disease outcome.…”
Section: Introductionmentioning
confidence: 99%